2020
DOI: 10.11606/issn.2317-0190.v27i3a176447
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre aspectos físicos-funcionais, comportamentais e de saúde com o medo de cair em idosos comunitários

Abstract: O medo em cair é definido como uma preocupação exacerbada em cair na realização das atividades cotidianas. O conhecimento dos fatores associados ao medo de cair pode contribuir na elaboração de estratégias multidimensionais que visem reduzir futuras quedas nos idosos. Objetivo: Verificar a associação dos aspectos físicos-funcionais, comportamentais e de saúde com o medo de cair em idosos comunitários. Método: Tratou-se de um estudo transversal, com amostra aleatória probabilística, incluindo 308 idosos comunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Moreover, older adults with a musculoskeletal pattern had 2.03 (95%CI 1.13; 3.64) higher chances of presenting fear of falling in the present study. This is due to the fact that this pattern is strongly related to rheumatic and joint diseases, which may increase the risk of older adults developing fear of falling [29,35]. In addition, other studies show that musculoskeletal conditions such as pain and osteoporosis increase the chances of older adults presenting fear of falling by 1.76 (95%CI 1.02; 3.04) [51] and 2.04 (95%CI 1.60; 2.60) [52], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, older adults with a musculoskeletal pattern had 2.03 (95%CI 1.13; 3.64) higher chances of presenting fear of falling in the present study. This is due to the fact that this pattern is strongly related to rheumatic and joint diseases, which may increase the risk of older adults developing fear of falling [29,35]. In addition, other studies show that musculoskeletal conditions such as pain and osteoporosis increase the chances of older adults presenting fear of falling by 1.76 (95%CI 1.02; 3.04) [51] and 2.04 (95%CI 1.60; 2.60) [52], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that although no studies have been found so far that relate the different multimorbidity patterns with fear of falling in older adults, there are studies that have demonstrated the association of isolated diseases with this outcome [25][26][27][28][29][30]. According to these studies, fear of falling is associated with heart disease [25,30] (cardiopulmonary pattern), joint diseases [29,31] (musculoskeletal pattern), and obesity, diabetes mellitus, and systemic arterial hypertension [26][27][28] (vascularmetabolic pattern). However, there is no evidence whether the concomitant presence of diseases that have clinical and physiological manifestations in the same body system also negatively interferes with fear of falling.…”
Section: Introductionmentioning
confidence: 99%